Generalized Solutions of the Galilean Invariant Thermodynamically Compatible Conservation Laws Constructed Using Godunov's Ideas: Scientific Explanation - Ivanov, M. Ya.; Mamaev, V. K. (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
The Galilean invariant thermodynamically compatible conservation laws that admit a class of generalized solutions is analyzed. The main feature of the generalized solutions considered in this paper is that they describe smooth solutions with the kinetic energy and total pressure loss, which accompany the dynamic process of heat supply. The principal properties of the generalized solutions analyzed in Godunov's works are the Galilean invariance and thermodynamic compatibility of the original conservation laws under the closed mathematical formulation of the thermal gas-dynamic process.